Turbidity and water clarity improvement processes in marine environment - Ho, Cai Rong. (2010)
The presence of total suspended solids is one of the main reasons which cause turbidity in marine water. In order to obtain better quality water for uses, physical and chemical methods are employed to clarify the water. In this report, the chemical method of coagulation and flocculation will be discussed. Coagulants are added to destabilize the colloid particles and allow them to get together for easy removal. Chemical coagulants are usually used in water treatment processes but natural coagulants are gaining popularity as they are more environmentally friendly. Both are discussed to access their applicability to marine water treatment. Experiments using both raw and synthetic seawater are conducted to determine the optimal dosage range and efficiency by using aluminium sulphate (alum) and ferric chloride as coagulants. Factors such as salinity and temperature are also investigated to examine their relation to coagulation efficiency. The best conditions to maximize coagulation efficiency are deduced. The optimal dosage of alum was found to be approximately 40mg/L, while the optimal dosage of ferric chloride could not be determined due to lack of resources and time to explore further into methods for detecting total suspended solids in coloured solutions. Varying salinity in synthetic seawater was found not to affect the coagulation ability of alum. A higher temperature induced more rapid reaction rate leading to more effective coagulation. The applicability of the experiments for commercial uses on seawater near industrial areas in Singapore was assessed. In conclusion to the studies made in this report, alum will be a more suitable and feasible coagulant for commercial uses of coagulation and flocculation.